The Absence of Women in Modern Brazilian Theater - André, Carminda Mendes (2025)
The reflections expressed in this text aim to present a critical look at the concept of “modern” in Brazilian theater, especially in terms of the female presence. It problematizes the idea of ??Brazilian theater's backwardness through the analysis of three influential authors in the historiography of Brazilian theater: Sábato Magaldi, Gustavo Dória, and Décio de Almeida Prado. It is observed that these historical perspectives silence the presence of women as protagonists of scenic transformations, relegating them to a subordinate role. This is an essayistic text.